RUMAH SENI RUANG TERAPI - Herman Suyudhi; Alvin Hadiwono (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
Stress and Depression are problems that often occur in people's lives. One of the causes is one’s habit in spending most of their time working and resting at home and without social activities that can be done every day with other individual, furthermore with the existence of social media that makes humans able to communicate with electronic devices and not meeting directly. The main issue is "Open Architecture as a Third Place" which discusses how to create a place that can become a Third Place as a gathering place for communities to socialize and as an informal public place. Another issue raised is the Art of Therapy as an Access to mental changes in society which increases stress levels differently by using images in form, combining thoughts with one another, struggling alone through an object, movements that can be united with images can be made into an art performance space. The project location is on Jalan RS. Fatmawati Raya in South Jakarta, West Cilandak, which is known as one of the areas that are dominated by offices with high levels of stress and depression. The aim of this project is to create a Third Place that can be a gathering place for the community to provide comments and interaction space using seniors. The research methods used in this research are Field Survey, Literature Study and Precedent Study. The research results obtained are the design of the building as "House of Art Space Theraphy". The main programs in this project are Planting, Lounge, Drawing Art in Sand, FoodCourt, 3D Installation, Chalkzone Wall, Free Drawing Workshop, Acrylic Art Exploration, Floor Drawing and Art Gallery, Listening Pictures and Self-Recognition Reflections that want to be shown to seniors who are all what humans do arising from feelings of life and moving beautifully so as to divert human feelings to improve themselves. Keywords: art; community; mental; stress; third placeAbstrakStress dan Depresi merupakan permasalahan yang sering terjadi dalam kehidupan masyarakat. Hal ini disebabkan oleh salah satunya kebiasaan manusia dalam menghabiskan sebagian besar waktunya bekerja dan beristirahat di rumah dan tanpa adanya kegiatan sosial yang dapat rutin dilakukan setiap hari dengan sesamanya, apalagi dengan adanya media sosial yang membuat manusia dapat berkomunikasi hanya dengan perangkat elektronik dan tidak bertemu secara langsung. Isu utama yang diangkat adalah “Open Architecture sebagai Third Place” yang membahas tentang bagaimana menciptakan sebuah tempat yang dapat menjadi Third Place sebagai tempat berkumpulnya komunitas masyarakat untuk bersosialisasi dan sebagai tempat publik informal. Isu lain yang di angkat adalah Seni Terapi sebagai Akses perubahan mental masyarakat yang mengalami tingkat stress berbeda dengan menggunakan seni dalam bentuk gambar, membagikan pikiran satu sama lain, menyadari diri melalui suatu objek, gerakan yang dapat disatukan dengan gambar dapat di jadikan ruang pentas seni. Lokasi proyek berada di Jalan RS. Fatmawati Raya di Jakarta Selatan, Cilandak Barat, yang dikenal sebagai salah satu kawasan yang di dominasi dengan perkantoran dengan tingkat stress dan depresi yang tinggi. Tujuan dari proyek ini adalah menciptakan sebuah Third Place yang dapat menjadi tempat berkumpulnya masyarakat untuk berkomunitas dan ruang interaksi dengan menggunakan seni secara primer. Metode penelitian yang digunakan dalam penelitian ini adalah Survey Lapangan, Studi Literatur dan Studi Preseden. Hasil penelitian yang didapatkan adalah perancangan bangunan sebagai “Rumah Seni Ruang Terapi”. Program utama dalam proyek ini yaitu Planting, Relaxing Space, Drawingin Sand, FoodCourt, Instalation 3D, Chalkzone Wall, Free Drawing Workshop, Exploration Art Acrylic, Floor Drawing dan Art Gallery, Listening Drawing and Reflection Get to Know Self yang bertujuan untuk menghadirkan seni yang merupakan segala perbuatan manusia yang timbul dari hidup perasaannya dan bersifat indah hingga dapat menggerakkan jiwa perasaan manusia untuk memperbaiki diri.